Ekonomi Buddhis Kehidupan Bahagia Tinjauan Anguttara Nikaya IV, 285 - Hendri Hermawan; Alexander Candra (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
Purpose - This study raises the role of suttas in the Buddhist scriptures of Tripitaka (Anguttara Nikaya IV, 285) to be applied in everyday life. So as to contribute to the wider community, especially Buddhists. Design/methodology/approach This research method is qualitative descriptive using direct observation result, open interview and then take conclusion.Research Limitation/Implication - The limitation of this research lies in the honesty of respondents, and the involvement of obaservation in the sample is taken.